Numerical investigation of flammable cloud on liquid hydrogen spill under various weather conditions. (8th March 2018) - Shao, Xiangyu; Pu, Liang; Li, Qiang; Li, Yanzhong
Abstract: The investigations of hydrogen leakage during the latest decades, have developed our knowledge level. However, few studies concerned the whole dispersion history of the flammable cloud (from generating to disappearing in the atmosphere). A Non-Homogeneous Equilibrium Model (NHEM) was used, and validated by a large scale LH2 spill experiment. The predicted data displayed good agreement with the experiment. Moreover, the experiment was further investigated on the colourless flammable cloud. Three primary questions of the hydrogen dispersion process were concerned: the maximum spreading range, the minimum distance above the ground, and the duration time of the flammable cloud in the atmosphere. Three major influence factors were selected to simulate various weather conditions, including ambient temperature (coupled with ground temperature), wind speed and atmospheric pressure. The hydrogen dispersion can be excited with the increased wind speed, and be impeded with the increased atmospheric pressure. The hydrogen dispersion process in four seasons of a year appears a different trend. Highlights: The whole time history of the flammable cloud dispersion was focused. Invisible flammable cloud (4–6.7%, v/v) was further studied under test6 condition. The effects of three weather conditions on hydrogen dispersion were studied. The time history of minimum above ground distance of flammable cloud was studied.